Pendampingan Intensif Dosen dalam Meningkatkan Kualitas Pelaksanaan KKN Mahasiswa di Kabupaten Pangkajene dan Kepulauan - Andi Muhammad Rivai; Andhi Febisatria; Yusi Irensi Seppa; Siti Syarifah Wafiqah Wardah; Fatimah Akbal (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service activity aims to improve the quality of the implementation of the Kuliah Kerja Nyata (KKN) program through direct mentoring and counseling by lecturers in Pangkajene and Kepulauan Regency. The background of this activity is based on the persistence of several challenges in KKN implementation, including suboptimal program planning, limited student capacity in identifying community needs, and the lack of effective monitoring and supervision in the field. The implementation method employed an intensive mentoring and continuous counseling approach conducted directly by lecturers to students throughout the program. The stages included preparation, implementation of mentoring and counseling, as well as monitoring and evaluation. The results indicate an improvement in students’ ability to design community-based programs, implement activities systematically, and solve field-related problems adaptively. Mentoring also contributed to increased community participation and enhanced social interaction between students and the community. Overall, this activity demonstrates that the active role of lecturers in mentoring KKN significantly enhances the effectiveness of community service programs and strengthens the role of higher education institutions in sustainable community empowerment